(untitled) (Horizontes de Enfermería, 2025)
The new challenges for health systems worldwide are aimed at guaranteeing the quality of health services. In this study, carried out at the El Ángel Basic Hospital, the quality of nursing services was evaluated from the perspective of the users and the level of compliance with quality standards related to the care process. A non-experimental mixed methodological approach with a descriptive and cross-sectional design was adopted. The study population included nursing professionals and external users of emergency, gynecology, and surgery services from September to December 2023. A sample of 12 nurses and 140 users were selected through convenience and systematic sampling, respectively. The results revealed a demographic diversity among users, highlighting a worrying lack of health insurance affiliation. In addition, a generally positive perception was observed in aspects such as security and empathy, although areas such as reliability and responsiveness showed variable levels of satisfaction. Specifically, problems were identified in the availability of medications and equipment in the emergency service, as well as concerns in the response capacity and empathy in the surgery and gynecology services. These findings highlight the need for improvements to guarantee more effective and satisfactory care for users in different areas of the hospital’s nursing services.